Communication strategies to mobilize volunteers a case study on the operation blessing foundation Philippines (DAVAO) - Gabao, Charlene Joyce T.
Humanitarian organizations play a vital role in extending help to the needy people in the areas of Mindanao. These organization need support from volunteers because they serve as the lifeline of the organization. This research was done to identify the communication strategies to mobilize volunteers in a non-profit humanitarian organization namely Operation Blessing Foundation Philippines(Davao) and determine how is communication used to mobilize the core volunteers. Two staff and two core pastors were interviewed for the data analyses of the study. The questions formulated were related to the Operation Blessing Davao and its people as well as to the activities performed by the organization. The identified communication strategies were constant communication which involves texting, calling and sending letters, face-to-face communication or personal talk, ?send off? prayer day, round table discussion and charisma of pastors. Results of the study show that the organization was investing more on enhancing their good relationship with their core pastors. Communication, on the other hand, is used to maintain contact with organization's volunteers as well as for a participatory and interactive organizational environment.
Thesis, Undergraduate (BA Communication Arts) -- U. P. in Mindanao
Keywords: Communication Arts -- Speech Communication